Identification of Proteases and Protease Inhibitors in Seeds of the Recalcitrant Forest Tree Species Quercus ilex - Escandón, Monica; Bigatton, Ezequiel D.; Guerrero-Sánchez, Victor M.; Hernández-Lao, Tamara; Rey, Maria-Dolores; Jorrín-Novo, Jesus V.; Castillejo, Maria Angeles (Frontiers in Plant Science, 2022)
Proteases and protease inhibitors have been identified in the recalcitrant species Quercus ilex using in silico and wet methods, with focus on those present in seeds during germination. In silico analyses showed that the Q. ilex transcriptome database contained 2,240 and 97 transcripts annotated as proteases and protease inhibitors, respectively. They belonged to the different families according to MEROPS,1 being the serine and metallo ones the most represented. The data were compared with those previously reported for other Quercus species, including Q. suber, Q. lobata, and Q. robur. Changes in proteases and protease inhibitors alongside seed germination in cotyledon and embryo axis tissues were assessed using proteomics and in vitro and in gel activity assays. Shotgun (LC–MSMS) analysis of embryo axes and cotyledons in nonviable (NV), mature (T1) and germinated (T3) seeds allowed the identification of 177 proteases and 12 protease inhibitors, mostly represented by serine and metallo types. Total protease activity, as determined by in vitro assays using azocasein as substrate, was higher in cotyledons than in embryo axes. There were not differences in activity among cotyledon samples, while embryo axis peaked at germinated T4 stage. Gel assays revealed the presence of protease activities in at least 10 resolved bands, in the Mr range of 60–260 kDa, being some of them common to cotyledons and embryo axes in either nonviable, mature, and germinated seeds. Bands showing quantitative or qualitative changes upon germination were observed in embryo axes but not in cotyledons at Mr values of 60–140 kDa. Proteomics shotgun analysis of the 10 bands with protease activity supported the results obtained in the overall proteome analysis, with 227 proteases and 3 protease inhibitors identified mostly represented by the serine, cysteine, and metallo families. The combined use of shotgun proteomics and protease activity measurements allowed the identification of tissue-specific (e.g., cysteine protease inhibitors in embryo axes of mature acorns) and stage-specific proteins (e.g., those associated with mobilization of storage proteins accumulated in T3 stage). Those proteins showing differences between nonviable and viable seeds could be related to viability, and those variables between mature and germinated could be associated with the germination process. These differences are observed mostly in embryo axes but not in cotyledons. Among them, those implicated in mobilization of reserve proteins, such as the cathepsin H cysteine protease and Clp proteases, and also the large number of subunits of the CNS and 26S proteasome complex differentially identified in embryos of the several stages suggests that protein degradation via CNS/26S plays a major role early in germination. Conversely, aspartic proteases such as nepenthesins were exclusively identified in NV seeds, so their presence could be used as indicator of nonviability.